A Study on the Relationship Between Brand Value and Firm Value: The Case of Turkey - Arık, Ecem; Marangoz, Aslıhan Yavuzalp (Fırat University, 2025)
In rapidly changing and developing markets, there are many factors that help companies to have a strong position in the market. One of these is brand equity. In the most basic sense, brand equity is the total value of a brand in economic and social terms, as well as a value that shows the financial strength of the relevant brand. Therefore, firms aspire to create high brand equity, thereby strengthening their market position, competitive strategy and financial performance. Because firms with high brand equity have an advantage compared to their competitors in terms of consumer trust, differentiation, reputation, pricing power, customer loyalty, expanding market share, entering new markets, increasing firm value and access to more investors. In this context, in this study, the relationship between brand value and firm value of 49 firms listed in the Brand Finance 100 list, which ranks the firms with the highest brand value in Turkey between 2019 and 2023, and traded on the Borsa Istanbul 100 (BIST 100) is analyzed with the panel Granger causality test. The analysis reveals that there is unidirectional causality from brand equity to firm value. This finding shows that investors can better predict firm values by using the brand values of firms.

Hızla değişen ve gelişen piyasalarda firmaların pazarda güçlü konuma sahip olması üzerinde birçok faktör bulunmaktadır. Bunlardan biri de marka değeridir. Marka değeri en temel anlamda bir markanın ekonomik ve sosyal anlamdaki toplam değeri olmakla birlikte markanın finansal gücünü gösteren bir değerdir. Dolayısıyla, firmalar yüksek marka değeri yaratmayı arzulamaktadır. Firmalar bu şekilde piyasadaki konumunu, rekabet stratejisini, finansal performansını güçlendirmeyi amaçlamaktadır. Çünkü yüksek marka değerine sahip firmalar tüketici güveni, farklılaşma, itibar, fiyatlandırma gücü, müşteri sadakati, pazar payını genişletme, yeni piyasalara girebilme, firma değeri arttırma ve daha fazla yatırımcıya ulaşma konularında rakiplerine göre daha avantajlı konumdadır. Bu bağlamda bu çalışmada 2019-2023 dönemleri arasında Türkiye’nin en yüksek marka değerine sahip firmalarının sıralandığı Brand Finance 100 listesinde yer alan ve Borsa İstanbul 100 (BİST 100)’de işlem gören 49 firmanın marka değerleri ile firma değerleri arasındaki ilişki panel Granger nedensellik testi ile incelenmiştir. Analiz sonucunda, marka değerinden firma değerine tek yönlü nedensellik olduğu belirlenmiştir. Bu sonuç, yatırımcıların firmaların marka değerlerini kullanarak firma değerlerini daha iyi öngörebilecekleri anlamına gelmektedir.
Marka Değeri ve Firma Değeri İlişkisi Üzerine Bir Araştırma : Türkiye Örneği
Keywords: Financial Economy; Finansal Ekonomi; Product and Brand Management; Ürün ve Marka Yönetimi